Photomask Technology 2022 2022
DOI: 10.1117/12.2645402
|View full text |Cite
|
Sign up to set email alerts
|

Towards improving challenging stochastic defect detection in SEM images based on improved YOLOv5

Abstract: With the progression of deep learning algorithms in computer vision, a lot of research is taking place in the semiconductor industry towards improving real-time defect detection and classification analysis. An Automated Defect Classification and Detection (ADCD) framework not only enables rapid measurement of dimensions and classification of defects, but also helps minimize production costs, engineering time as well as tool cycle time associated with the defect inspection process. As we continue to shrink the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Future work should instead employ hyperparameter optimization algorithms such as genetic algorithms, grid search, or bayesian optimization. 6,13 Certain models do achieve better APs for the bridge and p-gap classes. Most notably, the Tiny model achieves a 36% better bridge AP than the default model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work should instead employ hyperparameter optimization algorithms such as genetic algorithms, grid search, or bayesian optimization. 6,13 Certain models do achieve better APs for the bridge and p-gap classes. Most notably, the Tiny model achieves a 36% better bridge AP than the default model.…”
Section: Resultsmentioning
confidence: 99%
“…1 This has spurred interest in machine learning, particularly deep learning (DL), methods that are able to handle noise and changes in scale better. [1][2][3][4][5][6] In this study, we focus on defect detection, which involves localizing and classifying defect instances, in SEM images. Dey et al 1 showed that a DL framework based on RetinaNet detects semiconductor defects more robustly than rule-based image processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…ML-based SEM defect detection methods, especially Convolutional Neural Network (CNN) models, are becoming popular due to their improved robustness to these variations. Two main paradigms for training defect inspection models exist, supervised 1,[17][18][19] and unsupervised [20][21][22] learning. Supervised learning, where an ML model learns by comparing its predictions to labels provided by a human expert, usually leads to the best performance for defect detection and classification.…”
Section: Semiconductor Defect Inspectionmentioning
confidence: 99%
“…The aforementioned object detection model families have been successfully applied to the semiconductor defect detection task as demonstrated in Ref. 3 and Ref. 16.…”
Section: Centernet Object Detection Frameworkmentioning
confidence: 99%
“…While several works have investigated the use of DL methods for semiconductor defect detection, [2][3][4] little work has pursued using DL techniques with lower inference time and smaller models. Ref.…”
Section: Introductionmentioning
confidence: 99%